The Group of Moscow 4302, the Painter of London F 6 and the Filottrano Painter — New Attributions - Vas’ko, Dmitrii S. (Actual Problems of Theory and History of Art, 2019)
The article attempts to supplement and clarify the current classification of late Attic red-figure vase-painting. A comparative stylistic analysis of the work of the Group of Moscow 4302 allowed us to conclude that they were made with the participation of one vase-painter, who should be refered to as the Painter of Moscow 4302, and the list of his works increased from 2 to 4. Some of the attributions made earlier were revised. The similarities with the works of the Master of London F 6, whose list of works has been proposed to be increased from 3 to 27, and the similarity of the latter with the works of the Filottrano Painter are revealed. All three vase-painters cooperated within one workshop.
Keywords: attribution; vase-painting; the Kerch style; pelike; krater